MARKET POWER AND EFFICIENCY OF ISLAMIC BANKING AND CONVENTIONAL BANKING IN INDONESIA - Chajar Matari Fath Mala; Ahmad Rodoni; Bahrul Yaman (Global Review of Islamic Economics and Business, 2018)
ASEAN Economic Community (AEC) of banking industry requires both Islamic and conventional banking to improve their efficiency because the competition in banking market industry will be more intense. Therefore, this study aims to identify the type of hyphotesis of industrial organization which exists in Islamic and conventional banks in order to investigate their readiness for AEC. The research sampling consists of 10 Islamic banks and 10 conventional banks from January 2009 to December 2016. To measure x-efficiency and scale efficiency, this research uses Data Envelopment Analysis (DEA). Meanwhile, the concentration is measured by Lerner index. The hypothesis is tested by using panel regression. The result shows SCP (Structure-Conduct-Performance) hypothesis is closely applied to Islamic and conventional banks because market concentration significantly influences profitability. RMP (Relative Market Power) hypothesis is also closely applied to Islamic and conventional banking, this indicates Indonesian banking has market power in determining prices and this condition makes the profit higher. RES (Relative Efficiency Structure) and SES (Scale Efficiency Structure) hypothesis do not exist in both conventional and Islamic banks because x-efficiency and scale efficiency do not affect profitability, concentration, and  market share simultaneously. Market power and efficiency researches are commonly conducted in conventional banking, however there are only a few research in Islamic banking area. The novelty of this study is the comparison between conventional and Islamic banking in the term of market structure and efficiency.